Kajian Hukum Tata Negara terkait Pembatasan Kebebasan Berpendapat di Media Sosial di Era Pandemi COVID-19: Pendekatan Deskriptif Kualitatif - Putra, Rengga Kusuma; Kriswandaru, Althea Serafim; Imaliya, Tri (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The COVID-19 pandemic has driven an increase in social media activity as a means of communication and expressing opinions, but it has also introduced new challenges to freedom of expression. This study aims to analyze policies restricting freedom of expression on social media during the pandemic from the perspective of constitutional law. A qualitative descriptive approach was employed, with data collected through in-depth interviews, focus group discussions (FGDs), and legal document analysis. The study involved 15 informants, comprising legal experts, human rights activists, and social media users. Findings indicate that 60% of informants consider the restriction policies to be ambiguous and prone to misuse, while 40% support these policies for maintaining social stability. In this context, the Electronic Information and Transactions Law (UU ITE) serves as the primary legal basis for these policies. Yet, its implementation is often criticized for conflicting with democratic principles and human rights. The study also reveals that while the policies have successfully reduced the spread of false information, their impact on freedom of expression is significant, including the removal of critical content targeting the government. This study highlights the need for more transparent, fair, and evidence-based policies to balance public protection and respect for individual rights. It contributes to constitutional law discourse by providing recommendations for policy revisions that are more responsive to the challenges of the digital era, particularly during crise